Agroecological Peculiarities of Winter Triticale Variety Vivate Nosivskyi. - Л. В. Дем'яненко; В. В. Москалець; Т. З. Москалець; Н. М. Буняк; В. І. Москалець (Plant Varieties Studying and Protection)
The article describes Agro-ecological features of winter triticale variety Vivate Nosivskyi developed by means of individual selection based on hybrid combination ([Avgusto x NE 312] x К 9844) at the Examination Facility of Nosivska Breeding and Testing Station ofChernigivIAPPIAAN and selected by quantitative (grain productivity, quantity and weight of grains per ear, cup weight of grain, 1000 kernels weight), qualitative (protein contain, «raw» gluten) parameters of grain yield, by adaptability to a range of causative agents, abnormal events in winter-spring and summer, lodging. It shows that bio-agents of microbe preparations Azospirillum brasilense и Achromobacter album 1122 on initial stages of development of winter triticale variety Vivate Nosivskyi plants enhance nitrogen and phosphor nutrition as reflected in raw and dry weight of plants increased by 1,5 to 2,5 times, area of leaf surface - 2 to 2,4 times, grain yield -1,1-1,3 times.